Damage resistance and open-hole strength of thin veneer laminates: Adopting design and testing principles from fibre-reinforced polymers. (January 2023) - Reiner, Johannes; Pizarro, Sergio Orellana; Hadi, Kenny; Narain, Darren; Zhang, Peng; Jennings, Matt; Subhani, Mahbube
Abstract: Bulky, thick solid wooden parts are typically used despite the fact that such cross-sections do not yield the optimal load transfer. This study investigates thin quasi-isotropic [ 90 / 45 / 0 / − 45 ] s Beech veneer laminates subjected to a range of mechanical tests derived from fibre-reinforced counterparts. The results of standard tension, open-hole tension and compact tension tests in combination with digital image correlation and cross-sectional microscopy reveal that Beech veneer laminates can be tested and analysed in the same manner as fibre-reinforced laminates, leading to consistent values of strength and damage resistance as a result of reliable and repeatable damage patterns. It is found that modulus (5.5 GPa), tensile strength (70 MPa) and open-hole strength as well as translaminar fracture energy (5 – 14 kJ/m 2 ) are one order of magnitude lower compared to fibre-reinforced polymer composites. Highlights: Successful application of veneer laminates to mechanical tests designed for FRPs. Open-hole and compact tension tests yield consistent results with small variation. Cross-sectional microscopy shows minor presence of delamination within laminates.